Marketing strategies in Vietnamese higher education in the digital context: some suggestions - Duong, Thi Hoang Yen (Đại học Quốc gia Hà Nội, 2020)
Digitalisation has transformed the way people seek and receive information, which has led to a transformation in marketing from a traditional approach to a digital approach. This is also the case in Higher Education, and this paper discusses marketing at Vietnamese Higher Education Institutions with a digital focus. Currently, Higher Education Institutions need to run effective digital marketing campaigns to attract and retain potential and suitable students. However, in Vietnam, these campaigns might not have been fruitful given that they seem to lack strategic planning and consistency, which can be seen through the cases of FTU, HU and VNUH. The methodology for this research was through observing each institution’s website and social media channels to evaluate how the 5 W’s of investigation were applied and what the shortcomings are. Based on these findings, two recommendations have been put forward so that Vietnamese Higher Education Institutions can run effective digital marketing campaigns. First, all institutions need to invest in the transformation from traditional marketing to digital marketing happen while having a good relationship with students, who are essentially their customers. Second, a detailed Content Marketing Strategy for each institution has been devised to make sure all critical aspects are covered in such strategy and make sure that the contents reflect reality and are of high value. Most importantly, building a good connection with them can enable Higher Education Institutions’ marketing campaigns to gain scalability with user-generated contents and word of mouth, which come from alumni and current students to potential students. Even though this paper has looked at digital marketing journey and how to run effective campaigns suitable for the current Vietnamese Higher Education context, it only looks at three universities as representatives from each university model in Vietnam. Therefore, recommendations for each institution need to be put forward based on a more specific and customized research. It is suggested, therefore, that each university should carry out the 5 W’s of Investigation to clearly define their campaigns and their Content Marketing Strategy. The information gathered, therefore, can become a valuable source for a more detailed marketing strategy entailing all the different kinds of sub-strategies as mentioned above. For example, knowing the customers’ online user personas can enable an institution to devise a relevant and successful online viral campaign.